Comparison of soft tissue chin thickness at different levels of chin in subjects with various growth patterns - Javed Sodawala; Amit Akolkar; Fatema Sodawala; Sumit Gandhi; Shaheen Hamdani; Sayyed Muhammad Ali (Indian Journal of Dental Research, 2020)
Aims and Objectives: To evaluate the association between mandibular growth pattern and soft tissue chin (STC) thickness measured at different chin levels and the gender differences in STC thickness at these different chin levels. Materials and Methods: Pretreatment lateral cephalograms of 161 subjects aged 18–45 years were selected, and subjects were divided into 4 groups depending on mandibular growth pattern defined by the mandibular plane to cranial base angle. The STC thicknesses were measured at pogonion (Pog), gnathion (Gn), and menton (Me). Group difference was evaluated using analysis of variance. Results: STC thickness was greater (p < .05) in the low-angle group, and it gradually decreased across the groups, the least being in the high-angle group. No sexual dimorphism was observed among the groups (p > .05). Conclusion: This study suggests that STC thickness measurements were smaller in high-angle group compared to low-angle group.